Industry 4.0 and Accounting: Challenges and Opportunities - Petrova, Petya (Research Papers, 2018)
The integration of contemporary information and communication technologies in industry changes requirements for companies to their management and financial information useful input for decisions about providing resources to an entity. This paper aims to focus on some guidelines of accounting` s development and improvement as a result of Industry 4.0. There is characterized the essence of cloud accounting, defined as a technology of future by using decriptive, logic and SWOT analysis.